Comparative study on modes I and II fracture characteristics of bituminous coal using asymmetric semi-circular bend specimen. (August 2022) - Zhao, Yixin; Sun, Zhuang; Teng, Teng; Wang, Wei; Noraei Danesh, Nima; Zhang, Cun
Highlights: The differences in the modes I and II fracture characteristics of coal was studied by using asymmetric semi-circular bend specimen. The notch length has a significant impact on peak load and fracture toughness, but it has a slight influence on crack propagation path. A method based on acoustic emission parameters is proposed to determine the real-time microscopic failure mechanism of specimens. Coal specimens experience tensile fracture (mode I) initiation under both mode I and mode II loading. Abstract: Modes I and II fractures of coal play an important role in coal mining and have a serious impact on coal production and the control of mining hazards. Therefore, asymmetric semi-circular bend (ASCB) specimens with different notch depths were used to carry out modes I and II loading tests. The differences in the modes I and II fracture characteristics of coal specimens were studied. The internal damage characteristics, surface displacement characteristics, failure mode and microscopic damage mechanism of bituminous coal specimens were analysed by acoustic emission (AE) and digital image correlation (DIC) methods. The results show that the fracture toughness of coal under mode II loading is 1.02 times greater than that under mode I loading. The crack initiates along the centreline of the specimen and propagates in a roughly linear form under mode I loading. Under mode II loading, the curved crack mainly initiates from the upper left of the ASCB specimens. The notch length has a significant impact on peak load and fracture toughness, but it has a slight influence on crack propagation path. Larger notch depths are more suitable for modes I and II ASCB fracture tests. In this study, a method based on AE parameters is proposed to determine the real-time microscopic failure mechanism of coal. Combined with AE and DIC methods, it is revealed that the coal specimens experience tensile fracture (mode I) initiation under both mode I and mode II loading, and no specimen can be initiated with mode II shear fracture under pure mode II loading. Mode II loading and mode II fracture are not equivalent.